Plasma Cardiac Troponin I Concentration and Cardiac Death in Cats with Hypertrophic Cardiomyopathy. (15th October 2014) - Borgeat, K.; Sherwood, K.; Payne, J.R.; Luis Fuentes, V.; Connolly, D.J.
<x xml:space="preserve">Abstract</x> Background The use of cardiac biomarkers to assist in the diagnosis of occult and symptomatic hypertrophic cardiomyopathy (HCM) in cats has been established. There is limited data describing their prognostic utility in cats with HCM. Hypothesis Circulating concentrations of N‐terminal B‐type natriuretic peptide (NTproBNP) and cardiac troponin I (cTnI) predict cardiac death in cats with HCM. Animals Forty‐one cats diagnosed with HCM at a veterinary teaching hospital, between February 2010 and May 2011. Methods Prospective investigational study. Plasma samples were collected from cats diagnosed with HCM and concentrations of NTproBNP and cTnI were analyzed at a commercial laboratory. Echocardiographic measurements from the day of blood sampling were recorded. Long‐term outcome data were obtained. Associations with time to cardiac death were analyzed using Cox proportional hazards models. Results When controlling for the presence/absence of heart failure and echocardiographic measures of left atrial size and function, cTnI > 0.7 ng/mL was independently associated with time to cardiac death. In univariable analysis, NTproBNP > 250 pmol/L was associated with cardiac death (P = .023), but this did not remain significant (P = .951) when controlling for the effect of clinical signs or left atrial size/function. Conclusions and Clinical Importance Plasma concentration of cTnI (cutoff >0.7 ng/mL) is a predictor of cardiac death in cats with HCM that is independent of the presence of heart failure or left atrial dilatation.